2003
DOI: 10.1007/s00347-003-0828-9
|View full text |Cite
|
Sign up to set email alerts
|

Phantomschmerz nach Enucleatio bulbi

Abstract: Phantom eye pain is present in nearly 1/4 of patients after enucleation and is significantly related to other perioperative pain symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
2
7
1
1
Order By: Relevance
“…In our study, there is a high correlation between ophthalmic pain before EA and phantom pain afterwards (p = 0.004, Fisher's exact test). This has previously also been reported by So¨ro¨s et al (Gerding et al 2003;Soros et al 2003). However, if we took the 59 patients who had an EA because of pain -add the 18 patients that stated they had ophthalmic pain before surgery -we find no correlation (p = 0.145, Fisher's exact test).…”
Section: Identification Of Risks Factors For Developing Phantom Painsupporting
confidence: 80%
See 4 more Smart Citations
“…In our study, there is a high correlation between ophthalmic pain before EA and phantom pain afterwards (p = 0.004, Fisher's exact test). This has previously also been reported by So¨ro¨s et al (Gerding et al 2003;Soros et al 2003). However, if we took the 59 patients who had an EA because of pain -add the 18 patients that stated they had ophthalmic pain before surgery -we find no correlation (p = 0.145, Fisher's exact test).…”
Section: Identification Of Risks Factors For Developing Phantom Painsupporting
confidence: 80%
“…Previous studies of phantom eye pain have found the same incidence as in the current study (Nicolodi et al 1997;Gerding et al 2003;Soros et al 2003). The frequency of pain reported in the current study is different from the study by Gerding et al (2003), in which 71% of the patients had phantom pain less than once a month (Gerding et al 2003). The explanation for this difference may be that they found a lower frequency, because they used a self-report questionnaire and had lower participation rates.…”
Section: Phantom Pain After Eacontrasting
confidence: 56%
See 3 more Smart Citations